A Review Study of Biofilm Bacteria and Microalgae Bioremediation for Palm Oil Mill Effluent: Possible Approach - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus; A. A., Azoddein (IOP Publishing, 2020)
It was known where water is, there is a life, but presently, water is the primary source of diseases, viruses, and microbes. Before the industrial revolution, freshwater was available in vast quantities and everywhere, but the unwell treatments of wastewater have contaminated our fresh water. The palm oil industries discharge palm oil mill effluent (POME) under the forced standards, but it still pollutes the freshwater because it streams contaminated water, and not freshwater. There are many methods for wastewater treatment, but most of it reached its maximum effort, for example, physical technologies probably can give 90% removal of total pollutants with high capital cost. Hence, industries are trying to evolve biological treatments such as microalgae, and biofilm because of being friendly, and cost-efficient. This article reviews microalgae and biofilm bacteria ability for POME processing, and what possible advantages or valuable byproducts can produce. It concluded that uniting both treatments can lead to outstanding performance defeating withdraws and limitations.